Capillarisin inhibits iNOS, COX-2 expression, and proinflammatory cytokines in LPS-induced RAW 264.7 macrophages via the suppression of ERK, JNK, and NF-κB activation. (February 2013) - Han, Suckbae; Lee, Jong Hyun; Kim, Chulwon; Nam, Dongwoo; Chung, Won-Seok; Lee, Seok-Geun; Ahn, Kyoo Seok; Cho, Somi K.; Cho, Moonjae; Ahn, Kwang Seok
<x xml:space="preserve">Abstract</x> The aerial parts of Artemisia capillaris (Compositae) have been used in traditional Korean medicine as a cholagogic, antipyretic, anti-inflammatory, and diuretic purposes. In our previous study, ethanolic extracts of the plant demonstrated a marked anti-inflammatory effect in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells (J. Korean Soc. Appl. Biol. Chem., 2010, 53, 275–282). In the present study, capillarisin (CPS), a flavone, main constituent of A. capillaris, was examined for its anti-inflammatory activity in the cells. We found that CPS highly suppressed LPS-induced nitric oxide (NO) without exerting cytotoxic effects on RAW 264.7 cells. CPS inhibited the expression of LPS-induced inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) protein and their mRNA in a dose-dependent manner. Also, tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-1β, and prostaglandin E2 (PGE2) secretion were decreased by CPS in LPS-stimulated macrophages. As a result, CPS inhibited proinflammatory cytokines, iNOS, and COX-2, which is attributed to the suppression of LPS-induced ERK, JNK, and nuclear factor-κB (NF-κB) activation. Therefore, we demonstrate here that CPS potentially inhibits the biomarkers related to inflammation through the abrogation of ERK, JNK, and NF-κB p65 activation, and it may be a potential therapeutic candidate for the treatment of inflammatory diseases.